Assessment of the Drought Situation in Kerman Using Drought Indicators and its Relationship with the State of Vegetation Change in the Region - َAhmad Mazidi; Foroogh Mohammadi Ravari; Zahra Behzadi Shar Babak (Nīvār)
The purpose of this research is to analyse the drought situation of Kerman city using standardized precipitation drought indices , normal precipitation percentage and Palmer drought intensity and the relationship between these indices with the vegetation of the region. For this purpose, 30yeard of temperature and precipitation data (1988-2017) were obtained from the Iran Meteorological website to determine the value of (SPI) and (PNPI). In order to check the severity of drought, SPDI index was used. In addition, the map and diagram of the vegetation trend were prepared using GIS software and Google Earth Engine. The results showed that the SPI index of Kerman was mostly around the axis of -1 to +1, which represents a mild drought, and the PNPI of Kerman recognized most of the years as normal with 43%, and the Palmer index also showed that the years (2008-2004) 2010) have experienced a very severe drought with an intensity of about 4.8. Finally, the NDVI index showed that the maps obtained from satellite images show a decrease in vegetation of about 15 km, and according to the time series chart of 2008 and 2012, they had the lowest vegetation cover with an area of about 3 to 4 km. Therefore, due to the fact that the drought indicators examined in this study show the increasing trend of the intensity and duration of the drought and the vegetation map of the region has seen a decrease in area and the NDVI trend has been decreasing,